The long water - Penney, Stef (Quercus, 2024)
It is May in what was once a prosperous mining community. The snows are nearly gone and it's a time of spring and school-leavers' celebrations - until Daniel, a popular teenage boy, goes missing. Conflicting stories circulate among his friends, of parties and wild behaviour. As the search for Daniel widens, the police open a disused mine in the mountains. They find human remains, but this body has been there for decades, its identity a mystery. Everyone in this tight knit, isolated community is touched by these events: misanthropic Svea, whose long life in the area stretches back to the heyday of the mines, and beyond. She has cut all ties with her family, except for her granddaughter, Elin, an outsider like her grandmother. Elin and her friend Benny, both impacted by Daniel while he was alive, become entangled in the hunt for answers, while Svea has deep, dark secrets of her own.